2020
DOI: 10.1177/1321103x20929709
|View full text |Cite
|
Sign up to set email alerts
|

‘Turn up the volume and listen to my voice’: Students’ perceptions of Music in school

Abstract: Music teachers are often faced with students’ negative attitudes towards Music as a school subject, and dilemmas of what would be most important to teach and at the same time interesting, useful and relevant to students. Looking at music teaching and learning through the eyes of students can play a key role in re-shaping the condition of learning and promoting a positive and motivating musical learning environment. The aim of this study was to ‘turn up the volume’ of secondary students’ views of their music le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 34 publications
3
10
0
Order By: Relevance
“…Participants’ ratings on the Affiliation, Teacher Support, and Rule Clarity subscales of the CES suggest even more positive perceptions of the strong bond between classmates, the supportive and caring behavior of the music teacher, and the clarity with which the rules of the classroom and the consequences of breaking them were conveyed. The importance of affiliation to participants corroborates research highlighting the value placed by secondary school students on peer learning and making music with their classmates (Economidou Stavrou et al, 2020; Economidou Stavrou & Papageorgi, 2021). The importance of teacher support to participants reflects views of the ideal teacher as empathic and attentive (Arnon & Reichel, 2007; Wis, 2002), as someone creating an environment of service and community (Steele, 2010); and as a servant–leader (Wis, 2002).…”
Section: Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…Participants’ ratings on the Affiliation, Teacher Support, and Rule Clarity subscales of the CES suggest even more positive perceptions of the strong bond between classmates, the supportive and caring behavior of the music teacher, and the clarity with which the rules of the classroom and the consequences of breaking them were conveyed. The importance of affiliation to participants corroborates research highlighting the value placed by secondary school students on peer learning and making music with their classmates (Economidou Stavrou et al, 2020; Economidou Stavrou & Papageorgi, 2021). The importance of teacher support to participants reflects views of the ideal teacher as empathic and attentive (Arnon & Reichel, 2007; Wis, 2002), as someone creating an environment of service and community (Steele, 2010); and as a servant–leader (Wis, 2002).…”
Section: Discussionsupporting
confidence: 70%
“…The ad hoc questionnaire consisted of items requiring closed- and open-ended responses. Only the former are reported in this article as the data from the open-ended responses are reported by Economidou Stavrou and Papageorgi (2021). Data relevant to the current study included demographic information (sex, age, year of study), achievement grade, and reported enjoyment of and motivation for school music lessons.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations